The Influence of English Translated Manga to Students’ English Reading Comprehension - Wahyu Budi (Journal of Research in Business, Economics, and Education, 2020)
The massive popularity of manga (Japanese comic) has led it to be translated into different languages, one of them is English. Despites the origins, English translated mangas are authentic English literature because they are written by a team of a bilingual Japanese-English translator and a native English-speaking translator-editor, who ensures that the text is natural and meaningful. This research aims to probe the influence of English translated manga to English reading comprehension among Indonesian High School students who frequently read English translated mangas. By using a questionnaire, 15 students were used as respondents. The research questions are related to their activity of reading mangas and their reading skills that they acquired from reading mangas. Statistically, the results showed H1 was rejected. Nevertheless, it showed that there are influences, yet the influences are so slight they did not meet the standard adequacy for signifying that a hypothesis is accepted.